Constantinopolis, Istanbul: cultural encounter, imperial vision, and the construction of the Ottoman capital - Kafescioğlu, Çiğdem (Buildings, landscapes, and societies, 2009)
Between Edirne and Kostantiniyye: the city's first Ottoman years -- Constructing the city: the architectural projects -- The urban program and Mehmed's foundation -- The patronage of the new ruling elite -- Memory, space, and vision in constructions of the Ottoman capital city -- Representing the city: Constantinople and its images -- Istanbul inhabited -- Epilogue: a picture from circa 1537